Alternative Road Economic Feasibility Study Medan-Berastagi Via Tuntungan Intersection-Sibolangit - Amrizal, Amrizal; Kusumadi, Kusumadi; Fadli, Fadli; Samiran, Samiran (International Journal of Science, Technology & Management, 2023)
As a sustainable from the research in 2019 regarding the Planning of the Medan-Berastagi Alternative Route that the Researchers have carried out, this year it is planned to conduct research related to the cost of construction and the feasibility of constructing the alternative route as a whole economy. It is important that a study be carried out immediately because of the importance of this alternative route considering the frequent occurrence of severe traffic jams due to accidents or natural disasters along this route in recent times. Knowing the development costs as well as the economic feasibility of this new route will help interested stakeholders in making decisions regarding this new route. The total construction cost which includes construction costs, design and supervision costs and land acquisition costs is IDR 1,171,518,647,736 while the annual routine maintenance costs are IDR 3,114,325,566 and periodic maintenance costs per five years are IDR 87,808,542,710. Calculation of Vehicle Operating Costs (VOC) is carried out by referring to Pacific Consultant International (PCI) standards while the Time Value calculation is adopted from the 2001 Bina Marga “Heavy Loaded Road Improvement Project – Master Plan Review” study (for Buses and Passenger Cars) and “Sumatera Region Road Project” PU (2000) for trucks. The existence of the Medan-Berastagi alternative road will save VOC of IDR 22,120,269,410 and Time Value savings of IDR 57,337,666,839 in 2023. The economic feasibility analysis results can be seen that the value of the Economic Internal Rate of Return is 12,06% greater than the current lending rates are in the range of 8-9%. At the prevailing interest rate of 10%, the Benefit Cost Ratio is 1.16 and the Net Present Values are IDR 204,496,000,000. These results indicate that the construction of the MedanBerastagi Alternative Road is economically feasible.